Criteria supporting the study of drugs in the newborn - Ward, Robert M.; Benitz, William E.; Benjamin, Daniel K.; Blackmon, Lillian; Giacoia, George P.; Hudak, Mark; Lasky, Tamar; Rodriguez, William; Selen, Arzu (Clinical therapeutics, 2006)
Profound changes in the development and the maturation of neonates' organs and organ systems over variable periods of time potentially place neonates at increased risk and/or at different risks compared with adults or older children on exposure to pharmaceutical agents. Most studies of drugs in neonates focus on pharmacokinetic and pharmacodynamic end points and include insufficient numbers of patients to permit evaluation of safety. Only one fourth to one third of approved drugs have received adequate pediatric study to permit labeling for treatment of all appropriate pediatric populations. The initial goal of the Newborn Drug Prioritization Group was to develop a reproducible, objective process for evaluating drugs most in need of study in the neonatal population based on a universally acceptable priority ranking. The criteria would be applicable across therapeutic classes and would identify those drugs for which immediate study was most needed. Because the therapeutic requirements of the neonate are unique in comparison to older infants and children, the National Institute of Child Health and Human Development and the US Food and Drug Administration (FDA) developed the Newborn Drug Development Initiative to address the limited study of off-patent drugs in newborns. In March 2003, they convened a meeting of pediatric pharmacologists and pediatric specialists from the FDA, the American Academy of Pediatrics, the National Institutes of Health, and academic institutions to discuss how to increase the study of drugs for the newborn. One of the working groups was charged to develop generic criteria for overall prioritization of drugs for study in newborns. Because resources are limited, and not all drugs identified by the 4 clinically focused working groups can receive study at the same time, a process for priority ranking is necessary. The panel identified 4 general categories containing different numbers of criteria as important for ranking drugs for priority investigation: (1) the disease and indication, including elements such as the potential for adverse outcomes, frequency in newborns, and level of evidence for treatment of newborns; (2) drug characteristics, including elements such as duration of dosing, lack of age-appropriate formulation, clinically relevant drug-drug and drug-disease interactions, and drug disposition in newborns; (3) feasibility and methodology for newborn studies, including both analytical considerations and clinical end points; and (4) the ethical basis for study, including elements to address benefit or harm due to exposure to the study drug, study methodology, and benefit of the new treatment relative to established standard therapy. Based on these categories, a list of criteria to warrant study of a drug in newborns was developed. A process for judicious use of limited resources to rectify these deficiencies remains an urgent public health need.